FENOMENA SURROGATE MOTHER (IBU PENGGANTI) DALAM PERSPEKTIF ISLAM DITINJAU DARI HADIS - Nurul Alifah Rahmawati; Hirma Susilawati (Research Institute and Community Engagement of IAIN MADURA, 2017)
In this modern era, there is a finding in technology in the field of genetically changes which try to help the married couple with no children for a long time of marriage. This change can be seen in the existence of an infant with infitro fertilization, sperm banks, or magic box that can save sperm and ovum as they are in the real womb. As the time is gone, the practice of infant with infitro fertilization and artificial insemination have developed in some forms of activity which are forbidden in Islam. One of the forbidden forms is infitro insemination or artificial insemination which uses the sperm and ovum from a marriage couple and put it in another woman’s womb. This practice is called as Surrogate Mother. Actually there is no verses in the al-Qur’an which strictly stated about the prohibition on the practice of infitro infant using another woman’s womb (Surrogate mother). But it does not mean that al-Qur’an does not give any solution and also guidance in solving the law of this problem. There are some syar’i theorems that can be used as references in the issue of surrogate mother, for example Q.S Maryam verse 3-5 which give us command to keep praying and trying to get descendents, Q.S al-Baqarah verse 223 which states that a wife is the best place for farming and also hadith of the prophet Muhammad SAW which forbid a man to give his sperm to another woman who is not their wife. Moreover, the practice of this surrogate mother is also contradictory with with al-maqasid al-shariah because it can cause a mixed Nasab. Based on those reasons, the writer is interested in analyzing how is the surrogate mother phenomenon in the view of hadith and its contextualization dealing with the children’s position in the law of Waris (inheritance). Based on the literature analysis done by the writer, it can be concluded that the practice of surrogate mother is forbidden according to Ulama because it gives more mudharat (negative effects) than Manfaat (Positive effect). The hadith used belongs to Hasan hadith with 48,9% percentage. While talking about the child’s position born through surrogate mother, they will be called as adopted children who substitute the position of their own children although they get the sperm and ovum from the real parents.